Protein kinase A is a dependent factor and therapeutic target in mouse models of fibrous dysplasia - Zhongyu Liu; Lu Xing; Wenlong Huang; Ning Ji; Hang Zhao; Qianming Chen; Xianglong Han; Ding Bai; Xuefeng Zhao (Nature Communications)
Abstract Fibrous dysplasia is a skeletal disorder caused by activating mutations in Gαs, leading to bone fractures, deformities, and pain. Protein kinase A (PKA), the principal effector of Gαs, plays critical roles in various biological processes. However, its role in fibrous dysplasia is unknown. Here we demonstrate that PKA activation replicates fibrous dysplasia-like lesions in a transgenic mouse model expressing an activating mutation of PKA in the skeletal stem cell lineage. Mechanistically, PKA promotes osteoclastogenesis and aberrant osteogenic differentiation and proliferation of skeletal stem cells, while impairing mineralization. Downregulating PKA activity, using either a genetically engineered PKA inhibitor peptide or small-molecule inhibitors, effectively alleviates fibrous dysplasia lesions in a fibrous dysplasia mouse model and safeguards bone structure by increasing trabecular bone volume in a PKA-inhibition mouse model. Although long-term pharmacological PKA inhibition remains untested, these findings demonstrate that PKA is a dependent factor in fibrous dysplasia initiation and progression, underscoring its potential as a therapeutic target.